PENGARUH ANTARA PENGAMBILAN RISIKO, BERSIANG AGRESIF MENGEJAR PRESTASI, INOVATIF, KEPUASAN KERJA DAN KECERDASAN ENTREPRENEURIAL (STUDI PADA PERWIRA MENENGAH DI MARKAS BESAR TENTARA NASIONAL INDONESIA ANGKATAN LAUT- JAKARTA) - Akhmad Tarmizi; Tjiptogoro Dinarjo Soehari (Akademika : Jurnal Teknologi Pendidikan, 2015)
Basically, job satisfaction is an individual thing. Each individual member of theArmed Forces of Indonesia - particularly the Navy will have a level of satisfaction variesaccording to the value system that applies to him. This study aimed to analyze the effects thatoccur among the risk taking, compete aggressively pursue achievement, innovative attitude,job satisfaction and entrepreneurial intelligence medium officers Indonesian Navy (the rankof Commandert and Lieutenant-Commander) in the environment MABESAL Cilangkap -Jakarta .Sampling addressed the 120 persons Major and Lieutenant-Colonel of 80 peoplefrom the existing amount. Of the 5 main variables of research is raised 52 manifest variablesor observations. The number of valid questionnaires were further processed as many as 200copies. The data were processed with descriptive analysis, cross tabulation analysis,confirmatory factor analysis, analysis of the structural model are summarized end with thetest of the hypothesis.The results that test the 7th hypothesis proved significantly. Factors ofrisk taking, compete aggressively pursue achievement, and innovative significantly influencejob satisfaction. Factors of risk taking, compete aggressively pursue achievement, andinnovative also significantly influence entrepreneureurial intelligence. Job satisfactionfactors significantly influence entrepreneurial intelligence. Further discussion of therecommendations for improvement and development potential risk taking, competeaggressively pursue achievement, innovative, entrepreneurial intelligence and job satisfationin MABESAL environment.